Steamboat PROSPECTOR and crowd of men on Dawson dock awaiting her departure, Yukon Territory, ca. 1902. - University of Washington Libraries. Special Collections Division
PH Coll 246.199 [Meed journal: ""Prospector" at Dawson just proceeding a departure."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number